(untitled) (Research, Society and Development, 2021)
Among the biotic factors that contribute to low crop productivity, losses caused by diseases, pests and weeds are those that require the greatest effort to control. The use of allelopathy is a tool that meets this need for biological control. Therefore, the objective of this work was to investigate the allelopathic potential of Zingiber officinale Roscoe extract on sourgrass seed germination. For this, the germination test was carried out in a completely randomized experimental design with 5 treatments and 4 replications. The treatments were based on the evaluation of the allelopathic effect of 4 concentrations of the aqueous extract of ginger, namely: 1.0%, 0.75%, 0.50% and 0.25. As control, a 1.0% Tween 80 solution and distilled water were used. The evaluation of the allelopathic potential of the extract was performed by determining the germination percentage and the germination speed index (IVG). The results showed that the increase in the concentration of the extract promoted a greater inhibitory effect on germination, suggesting, therefore, an allelopathic effect of the ginger extract on sourgrass seeds.